Legal regulation of the implementation of human rights in the educational environment - Shakirova, A.B.; Lavnichak, A.; Veselskaya, N.R (Bulletin of the Karaganda University “Law Series”, 2022)
The article reveals the legal mechanism of the realization of human rights in the educational environment and examines the main features of this institution. Topical issues of legal consolidation and practical realization of human rights in the field of education are considered, ways of solving the problems of implementing full and high-quality provision of the constitutional right of citizens to education in the conditions of the development of the rule of law and civil society are proposed. On the basis of general and special scientific methods of cognition, the analysis and generalization of theoretical and empirical material is carried out. The result of the study is to identify trends in the development of legal regulation of human rights in the educational environ-ment and to determine the prospects for further modernization of legislation in the field of education. Human rights in the field of education regulate public relations related to any forms of education and upbringing and form legal mechanisms for the realization of human rights. The purpose of the study is to develop ways to improve the legal regulation of human rights in the educational environment, taking into account the peculia r-ities of the protection and enforcement of human rights in this area, as well as the formation of specific recommendations for the systematic modernization of legislation on education in the Republic of Kazakhstan.